2022
DOI: 10.1007/s11218-022-09739-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19’s impact on learning processes in Australian university students

Abstract: The novel coronavirus SARS-CoV-2 (COVID-19) has accentuated the role and interplay of numerous educational factors, inviting pedagogical research concerning online education. Using self-determination theory's basic psychological needs and fundamental learning theories, identified educational factors were integrated into three pathways: (1) autonomy, technology acceptance, and self-regulation of learning; (2) relatedness, authentic happiness, and a classroom community; and (3) competency, harmonious passion, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 98 publications
0
10
1
Order By: Relevance
“…Furthermore, in our study, the students were satisfied with the support given by the teachers during the pandemic. This is in sharp contrast to the findings of the study, which reported that teachers faced many difficulties in supporting students due to a lack of experience in online teaching [ 25 ]. A possible explanation for the superior satisfaction observed in our study could be the extensive training provided to the teachers by our university’s deanship of learning and distance education.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, in our study, the students were satisfied with the support given by the teachers during the pandemic. This is in sharp contrast to the findings of the study, which reported that teachers faced many difficulties in supporting students due to a lack of experience in online teaching [ 25 ]. A possible explanation for the superior satisfaction observed in our study could be the extensive training provided to the teachers by our university’s deanship of learning and distance education.…”
Section: Discussioncontrasting
confidence: 99%
“…Participants discussed their experiences of seeking support from a teacher and speci cally highlighted times when they felt they were being "handballed" to the wellbeing team, resulting in these participants feeling unheard and invalidated. When students have a respectful and trusting relationship with their teacher, they are more likely to engage in proactive learning behaviours, which have a positive effect on their academic success [29]. Furthermore, literature on school belongingness highlights that teachers are pivotal sources in promoting a student's sense of belonging, even more than their peers [28].…”
Section: Discussionmentioning
confidence: 99%
“…Teachers may also consider allowing students more exibility in the use of technology in their classes and assessment tasks. Increasing technology use for students may assist students in engaging with their schoolwork and keeping up with the workload [5,29]. Hence, being creative in nding ways to foster autonomy in their learning could be an important step to bridge the degree of exibility and autonomy that was present during online learning.…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…Examination of previous studies and research related to the emotion of learning and its effects on the organization and management of knowledge in distance learning environments [5,[32][33][34]36,38,48].…”
Section: Study Toolsmentioning
confidence: 99%
“…In contrast, Eckley et al [ 34 ] focused on examining the interplay between psychological needs fulfillment, educational factors, and students’ expectations of future grades amidst the COVID-19 pandemic. Through structural equation modeling, they found that meeting higher needs significantly predicted engagement in educational factors, which in turn fostered resilience, motivation, and effective learning mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%